Risk-Taking, Speaking Ability, and Australasian Parliamentary Debate; Do They Really Appertain? - Luthfiyyah, Roghibatul (Universitas Swadaya Gunung Jati, 2014)
The purposes of this study are: (1) to find out whether there is any positive correlation between risk-taking and Australasian Parliamentary English Debate; (2) to find out whether there is any positive correlation between apeaking ability and Australasian Parliamentary English Debate; (3) to find out whether there is any positive correlation between risk-taking, speaking ability, and Australasian Parliamentary English Debate of the fifthh semester students of English Education Department of Unswagati in academic year 2014-2015.This research is carried out at English Education Department of Unswagati Cirebon. This research was conducted in 3 months, from January to March 2015. The population of this research was the fifth semester students of English Education Department of Unswagati Cirebon. There were 80 students taken as sample for this study using random sampling technique. the data used for this study were collected using performance tests and questionnaire. The data gained from questionnaire and tests were then being analyzed using simple correlation and multiple linier regression.Based on the result of the study, it can be concluded that: (1) there is significant positive correlation between risk-taking and Australasian Parliamentary English Debate.